Couple‐based Intervention for Depression: An Effectiveness Study in the National Health Service in England. Issue 2 (4th December 2017) - Baucom, Donald H.; Fischer, Melanie S.; Worrell, Michael; Corrie, Sarah; Belus, Jennifer M.; Molyva, Efthymia; Boeding, Sara E.
Abstract : This study represents an effectiveness study and service evaluation of a cognitive behavioral, couple‐based treatment for depression (BCT‐D) provided in London services that are part of the "Improving Access to Psychological Therapies" (IAPT) program in England. Twenty‐three therapists in community clinics were trained in BCT‐D during a 5‐day workshop, followed by monthly group supervision for 1 year. The BCT‐D treatment outcome findings are based on 63 couples in which at least one partner was depressed and elected to receive BCT‐D. Eighty‐five percent of couples also demonstrated relationship distress, and 49% of the nonclient partners also met caseness for depression or anxiety. Findings demonstrated a recovery rate of 57% with BCT‐D, compared to 41% for all IAPT treatments for depression in London. Nonclient partners who met caseness demonstrated a 48% recovery rate with BCT‐D, although they were not the focus of treatment. BCT‐D was equally effective for clients regardless of the clinical status of the nonclient partner, suggesting its effectiveness in assisting both members of the couple simultaneously. Likewise, treatment was equally effective whether or not both partners reported relationship distress. The findings are promising regarding the successful application of BCT‐D in routine clinical settings. Abstract : Video Abstract